EPISTEMOLOGI PENAFSIRAN AYAT MUTASYĀBIHĀT DALAM AL-QUR’AN: ANALISIS KOMPARATIF ANTARA PENDEKATAN SALAF DAN KHALAF - Imelia Sahda Salsabilla; Wafa Hadiratul Qudsy; Suja’i Suja’i; Mustopa Mustopa (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the epistemology of interpreting mutasyābihāt verses in the Qur’an through a comparative approach between the Salaf and Khalaf paradigms. This study is motivated by methodological differences in understanding mutasyābihāt verses, which influence the construction of classical and contemporary Islamic exegetical thought. The research employs a library research method with a descriptive-analytical approach. Data were collected through documentation of classical and contemporary exegetical works, scholarly articles, books, and academic works relevant to the epistemology of exegesis and mutasyābihāt verses. Data analysis was conducted using content analysis by examining epistemological patterns, interpretive methods, and the use of reason in exegesis. The results of the study indicate that Salaf epistemology is oriented toward the authority of revelation, tradition, and the principle of tafwīḍ, with a tendency to uphold textual meanings to preserve the purity of creed. Conversely, Khalaf epistemology emphasizes the integration of revelation and reason through the method of takwil, resulting in an exegetical approach that is more contextual and adaptive to modern social and intellectual developments. This study found that both approaches share the same objective, namely preserving the purity of Islamic doctrine, although they differ in their epistemological strategies. This study contributes to the development of epistemological studies of exegesis by offering an integrative perspective that balances the validity of tradition with contextual relevance. The implications of this study highlight the importance of developing a moderate and multidisciplinary tradition of exegesis in addressing the dynamics of contemporary Islamic thought.